A GENERAL DESCRIPTION OF THE PROBLEM OF IMPROVING THE COUNTRY'S TELECOMMUNICATIONS NETWORK (Archive of Conferences, 2020)
The main trends in the development of the modern economy include the increase in the share of the non-productive sector through the development of Information Technologies, the improvement of the quality content of the material and technical base of the production sector, socio-economic processes based and oriented to active information cooperation, the development of the telecommunications services market, its complexity